PARKING LAND EVALUATION AND PLANNING AT THE KERENENG MARKET, DENPASAR CITY - Ni Ketut Sri Astati Sukawati; I Gusti Agung Gde Suryadarmawan (Unmas Press, 2022)
Kereneng Market is a place where the buying and selling process takes place, where most of the traders and buyers or the public who come to Kereneng Market use transportation services (vehicles) to get to the market. This activity resulted in an increase in the volume of vehicles entering the Kereneng Market area due to the activities that occurred, and even when the market caused congestion at the Kereneng intersection and its surroundings. To anticipate this, it is necessary to provide adequate and neatly arranged parking facilities so that they can provide the parking services desired by all parties. The method used in collecting data in this research is direct observation in the field by conducting a survey. The survey was conducted for 3 (three) days, namely on Friday, Saturday and Sunday. The results of the research on the characteristics of parking at Kereneng Market include parking volume, parking accumulation, parking turnover rate, average parking duration and parking index. After doing the research, it can be seen the characteristics of the parking for each vehicle, namely the average volume of motorcycles is5309.3vehicles, while for cars is 658 vehicles on average market day, the highest accumulation of parking for motorcycles occurs at 05.00 – 06.00 00 in the eastern Indonesia time zone which is 1245 vehicles, while for cars occurs at 07.00 – 08.00 00 in the eastern Indonesia time zone which is 138 vehicles. Based non the results of the research, it shows that the capacity of the Kereneng Market parking area is no longer able to meet the needs of parking users